Genetically Engineered Biologic Drugs in Management of Children with Bronchial Asthma - Svetlana V. Zaytseva; Anna U. Tomilova; Olga V. Zaytseva; Olga B. Voronina; Olga A. Murtazaeva; Valeriy A. Mukhortykh; Irina N. Tsymbal (Union of pediatricians of Russia, 2021)
Current article represents the modern clinical guidelines on management of severe bronchial asthma (BA) in children and practical use of genetically engineered biologic drugs. Clinical efficacy and safety of omalizumab has its special role. Efficacy analysis was carried out in real-life' clinical setting (considering high economical expenses of biological treatment) to estimate effective response predictors and principles of patients selection for such therapy. Two years of anti-IgE treatment experience in inpatient pediatric department settings demonstrates that omalizumab inclusion to treatment of children with severe asthma resistant to standard therapy allows to solve asthma symptoms, to forgo high doses inhaled glucocorticosteroids, to improve lung function parameters, and to increase significantly quality of life in 95% of our patients.